2017
DOI: 10.1007/s40778-017-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin and FAK Regulation of Human Pluripotent Stem Cells

Abstract: Purpose of reviewHuman pluripotent stem cells (hPSCs) are anchorage-dependent cells that can be cultured on a variety of matrices and express integrins and the machinery for integrin signaling. Until recently, there has been limited understanding of exactly how integrin signaling regulates pluripotent stem cell (PSC) behavior. This review summarizes our knowledge of how integrins and focal adhesion kinase (FAK) regulate different aspects of hPSC biology.Recent findingsThe latest research suggests that mouse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 83 publications
2
34
0
Order By: Relevance
“…Physical interactions with cells or the ECM can be transduced into biological signals and influence actin dynamics via mechanosensitive receptors, such as integrin receptors and GPCRs [70]. Evidence has shown that integrin heterodimers, α5β1, α6β1, and αvβ3, mediate interactions between ESCs and various ECM substrates [13,[71][72][73]; they also play an important role in the maintenance of pluripotency [74], and matrix stiffness regulates integrin binding [75]. Whereas GPCRs, including lysophosphatidic acid receptors (LPARs) and sphingosine-1-phosphate receptors (S1PRs), play a role in the YAP signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Physical interactions with cells or the ECM can be transduced into biological signals and influence actin dynamics via mechanosensitive receptors, such as integrin receptors and GPCRs [70]. Evidence has shown that integrin heterodimers, α5β1, α6β1, and αvβ3, mediate interactions between ESCs and various ECM substrates [13,[71][72][73]; they also play an important role in the maintenance of pluripotency [74], and matrix stiffness regulates integrin binding [75]. Whereas GPCRs, including lysophosphatidic acid receptors (LPARs) and sphingosine-1-phosphate receptors (S1PRs), play a role in the YAP signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are important signaling receptors that mediate the interactions of the cells with extracellular matrix (24). They are involved in multiple inflammatory responses, including coronary atherosclerosis, obesity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…*, p Ͻ 0.05. Integrin ␣ V ␤ 5 in M2 polarization transduction (24). The mechanism of the formation of integrin heterodimer has not been well-understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, upregulation of select core pluripotent markers has been observed in 3-D culture of mouse [36,54] as well as human ESCs [55,56], suggesting a dependence on scaffold composition and culture conditions. We have reported upregulation of select naïve pluripotent markers in primed [37] and naïve human ESCs In both mouse and human ESCs, focal adhesion and integrin signaling serve pleiotropic roles in anchorage, contractility, survival, proliferation as well as support or inhibition of self-renewal [63]. Our study revealed upregulation in 3-D grown cells of several genes such as FLNC, COL4, CAV1, and SERPINE1, as well as ITGB1, ILK, and AKT1, which have been reported to be associated with actin cytoskeleton remodeling [64], and integrin mediated focal adhesion activation [65], respectively.…”
Section: Discussionmentioning
confidence: 99%